Innovation Management in Education: Implementing a Smart School Ecosystem through Artificial Intelligence - Erwin Novriyanto; Dadang Jaenudin (PPSDP International Journal of Education, 2026)
The rapid advancement of Artificial Intelligence (AI) has accelerated digital transformation in education, yet many educational institutions continue to struggle with sustainable and meaningful AI integration. Existing initiatives often emphasize technological adoption while overlooking the organizational and managerial processes required to ensure long-term impact, particularly in teacher professional development. This study addresses this gap by examining how innovation management can facilitate the implementation of a smart school ecosystem supported by AI. This article employs a conceptual research approach, integrating insights from innovation management theory, smart school ecosystem literature, and AI-enabled educational practices. The analysis synthesizes prior empirical and conceptual studies to develop a coherent perspective on how governance structures, leadership practices, and organizational learning processes shape AI adoption in educational settings. The findings indicate that AI contributes effectively to teacher professional development only when embedded within a managed smart school ecosystem. Innovation management operates through three key mechanisms: strategic governance that aligns AI initiatives with institutional goals, organizational learning cultures that enable teachers to engage constructively with AI-generated feedback, and leadership-mediated adoption processes that build trust and capacity. Without these mechanisms, AI implementation risks becoming fragmented, technocratic, and unsustainable. This study contributes theoretically by positioning AI integration as an innovation management challenge rather than a purely technological one. Practically, it offers guidance for educational leaders and policymakers seeking to design AI-supported professional development systems that are adaptive, ethical, and sustainable. The article concludes by outlining directions for future research on innovation governance and AI-enabled learning ecosystems across diverse educational contexts.